Best Paper Selection (Yearbook of Medical Informatics, 2020)
Wang J, Liang H, Kang H, Gong Y. Understanding health information technology induced medication safety events by two conceptual frameworks. Appl Clin Inform 2019;10:158–67 https://www.thieme-connect.com/products/ejournals/abstract/10.1055/s-0039-1678693Lee JY, van Karnebeek CDM, Wasserman WW. Development and user evaluation of a rare disease gene prioritization workflow based on cognitive ergonomics. J Am Med Inform Assoc 2019;26(2):124–33 https://academic.oup.com/jamia/article/26/2/124/5235389Patterson ES, Su G, Sarkar U. Reducing delays to diagnosis in ambulatory care settings: A macrocognition perspective. Appl Ergon 2020 Jan;82:102965 https://www.sciencedirect.com/science/article/pii/S0003687019301826?via%3Dihub